FORMULASI MIKROPARTIKEL BERPORI DALAM POLI (D,L-Laktida) SEBAGAI SCAFFOLDDENGAN TEKNIK EMULSIFIKASI PENGUAPAN PELARUT - Fitriani, Lili; Suciati, Tri (Universitas Andalas, 2011)
ABSTRACT Poly (D,L-lactide acid) has been used as scaffold for tissue engineering. In this study, PDLLA microparticles were made into porous microparticles. Porous microparticles were proposed to reduce burst release of protein and to prevent diffusion of released protein into non-target tissue. Formulation of porous microparticles was made by water-oil-water (W1/O/W2) emulsification-solvent evaporation using gas foamed as porogen. Variations of the amount of sodium bicarbonate, volume of citric acid solution and time for homogenization were optimized to produce optimum formulation. Evaluation for this microparticles included morphology of particles, particle size distribution and porosity. Porous microparticle produced by ratio volume of acid : dichloromethane : poly(vynil alcohol) (PVA) = 1:3:3 and the ratio of sodium bicarbonate : PDLLA = 2:3 was the optimum formulation. Keywords :Porous Microparticles, PDLLA,Gas Foamed, Scaffold, Solvent Evaporation